2022
DOI: 10.1016/j.scitotenv.2021.150089
|View full text |Cite
|
Sign up to set email alerts
|

CO2 emissions and economic growth: Assessing the heterogeneous effects across climate regimes in Africa

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…Meanwhile, this also means that the rapid economic development of the E7 countries in the context of economic globalization has led to an increase in energy demand and thus to environmental degradation. The findings of Xiong and Xu ( 2021 ), Kirikkaleli and Adebayo ( 2021a ), and Espoir et al ( 2022 ), who found a long-term positive association between GDP and CO 2 emissions, are supported by this one.…”
Section: Empirical Results and Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Meanwhile, this also means that the rapid economic development of the E7 countries in the context of economic globalization has led to an increase in energy demand and thus to environmental degradation. The findings of Xiong and Xu ( 2021 ), Kirikkaleli and Adebayo ( 2021a ), and Espoir et al ( 2022 ), who found a long-term positive association between GDP and CO 2 emissions, are supported by this one.…”
Section: Empirical Results and Discussionmentioning
confidence: 56%
“…Liu et al (2020) examined the relationship among economic growth, governance, and carbon dioxide emissions within the framework of the “EKC” in five high carbon dioxide–emitting countries from 1996 to 2017, and found that political, economic, and institutional governance can improve the quality of the environment. Espoir et al ( 2022 ) used panel and time-series techniques to examine the heterogeneous effects of CO 2 emissions and temperature on incomes in Africa from 1995 to 2016. It was found that environmental policies specifically designed to reduce CO 2 emissions across Africa could have a significant impact on production in the long term.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By establishing a comprehensive infrastructure and ecosystem, alongside competitive resources, Malaysia can substantially reshape its industrial and investment landscape. However, this progress has come at a significant environmental cost, as there has been a continuous rise in economic development contributing to climate change issues [ 94 ]. In response, economies around the world are collaborating to find the best sustainability alternatives [ 95 ].…”
Section: Results and Policy Implicationmentioning
confidence: 99%
“…Recently, with the gradual increase in the study on the impact of climate change on various human activities, scholars have also begun to pay attention to the factors influencing climate change [58]. Although the factors affecting the growth of carbon emissions are complex and diverse, the economy, population, and S&T innovation are the three factors primarily considered by scholars [59].…”
Section: Research On Carbon Emissions Determinantsmentioning
confidence: 99%